Dairy cattle management: survey on dairy cattle lactation trend in Sabah - Bonaventure Boniface; Jupikely James Silip; Abdul Hamid Ahmad (University Library of Munich, 2010)
A survey was conducted to obtain information on Sabah dairy cattle lactation length and lactation yield to identify the lactation trend. In the study, 18 farms with 2 types of husbandry practice namely feedlot and grazing were visited. Dairy livestock has became established part of the livestock industry with Friesian Sahiwal crossbreed, imported from Australia and New Zealand with heredity of 62.5% Friesian 37.5% Sahiwal and 50% Friesian 50% Sahiwal respectively. Local born cattle are referred as Sabah Sahiwal Friesian (SSF). All the cows are milked twice a day. From the results obtained, the average lactation of dairy cow is around 6 liters to 12 liters per day with mean of 8.6 liters per day if there is no lactation failure. The mean for cow milked per lactation is 278 days of length and the mean for total milk yield per lactation is 2489 liters. Incidence of lactation failure happens in certain farm that had just received new imported cows, or happens in individual cow in the herd of lactating cows. The information of the survey has been obtained from selected farmers. Therefore the reliability of the data on certain aspects of dairy livestock was based on experience of farmers who provide the information.